The horse in the light of veterinary medicine and the Muslim tradition - A comparative study (VETERINARIA, 2023)
Of all the animals that accompany humans through almost all stages of human development, horses have the most prominent place. In addition to a presentation of the role and significance of horses in human life throughout history until today, taking the Bosnian mountain horse as a paradigm, a presentation is highlighted of the relationship of the Islamic religion to horses, which are the most valued domestic animals. In Islamic theology, caring for the animal world is mandatory, primarily as an expression of doing deeds that bring us closer to God, where the well-being of horses is especially important.
Keywords: Bosnia and Herzegovina; Bosnian mountain horse; Islam; mule; hinny